Novel Solutions Applied in Transseptal Puncture: A Systematic Review - Morais, Pedro André Gonçalves (2017)
Access to the left atrium is required for several minimally invasive cardiac interventions in the left heart. For this purpose, transseptal puncture (TSP) technique is often performed, perforating the atrial septum under fluoroscopic or/and ultrasound imaging guidance. Although this approach has been used for many years, complications/failures are not uncommon mainly in patients with abnormal atrial anatomy and repeated TSP. Thus, this study presents an overview of methods and techniques that have been proposed to increase the safety and feasibility of the TSP. A systematic review of literature was conducted through the analysis of the articles published between 2008 and 2015. The search was performed in PubMed, Scopus, and ISI Web of Knowledge using the expression "transseptal puncture." A total of 354 articles were retrieved from the databases, and 64 articles were selected for this review. Moreover, these 64 articles were divided into four categories, namely: (1) incidence studies, (2) intraprocedural guidance techniques, (3) preprocedural planning methods, and (4) surgical instruments. A total of 36 articles focused on incidence studies, 24 articles suggested novel intraprocedural guidance techniques, 5 works focused on preprocedural planning strategies, and 21 works proposed surgical instruments. The novel 3D guidance techniques, radio-frequency surgical instruments, and pre-interventional planning approaches showed potential to overcome the main procedural limitations/complications, through the reduction of the intervention time, radiation, number of failures, and complications.